2003
DOI: 10.1002/anie.200250816
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Mesoporous/Macroporous Metal Oxides Templated from Polyethylene Oxide Surfactant Assemblies

Abstract: Surfactant templating techniques based on electrostatic, hydrogen-bonding, covalent, and van der Waals interactions between organic and inorganic species have been developed for the synthesis of materials with a narrow mesopore size distribution and controlled pore structure. [1,2] The use of block copolymers was recently shown to extend the pore sizes of ordered mesoporous oxides up to ten nanometers. [3,4] In addition, macroporous materials with pore sizes ranging from 100 nm to 1 mm can be obtained using la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
94
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(99 citation statements)
references
References 36 publications
4
94
1
Order By: Relevance
“…The macrochannels are not interconnected with each other and perpendicular to the dense mesoporous shell as described in our recent paper. [35] This observation supports our formation mechanism proposal that the present meso-macroporous titania materials with mesostructured shell and macroporous core might be formed by combining a reverse micelle templating pathway with a conventional surfactant templating technique of a hybrid composite mesostructured phase. The mesopore size can be adjusted by changing the hydrothermal temperature (Fig.…”
supporting
confidence: 84%
“…The macrochannels are not interconnected with each other and perpendicular to the dense mesoporous shell as described in our recent paper. [35] This observation supports our formation mechanism proposal that the present meso-macroporous titania materials with mesostructured shell and macroporous core might be formed by combining a reverse micelle templating pathway with a conventional surfactant templating technique of a hybrid composite mesostructured phase. The mesopore size can be adjusted by changing the hydrothermal temperature (Fig.…”
supporting
confidence: 84%
“…For example, highly mesoporous crystalline TiO 2 macrocellular foams can be produced by combining a non-static air-liquid foam strategy and various mesogenic template methods [7]. Also, Blin et al have synthesized the macro/mesoporous zirconia and titania using polyethylene oxide surfactant [8]. Orilall et al reported a combined assembly of soft and hard chemistries to synthesize highly crystalline inverse opal macroporous Nb 2 O 5 and TiO 2 [9].…”
Section: Introductionmentioning
confidence: 98%
“…Many efforts have been taken to synthesize interconnected macroporous materials with mesoporous walls using simple techniques to enhance the performance of the materials for special applications [7][8][9][10][11][12][13][14][15][16]. For example, highly mesoporous crystalline TiO 2 macrocellular foams can be produced by combining a non-static air-liquid foam strategy and various mesogenic template methods [7].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one way to design porous materials consists of combining the sol-gel chemistry and the use of surfactant molecule assemblies as templates to create the pore network. Depending on the structure of the initial system, microporous, mesoporous, or macroporous materials are recovered [20][21][22][23][24][25][26]. For example, by this way mesoporous and macroporous materials can be synthesized from micelles [20][21][22] and emulsions [24][25][26], respectively.…”
Section: Introductionmentioning
confidence: 98%